Nurses' experiences of patient safety incidents in Korea: a cross-sectional study. Issue 10 (31st October 2020) - Choi, Eun Young; Pyo, Jeehee; Lee, Won; Jang, Seung Gyeong; Park, Young-Kwon; Ock, Minsu; Lee, Sang-Il
Abstract : Objectives: The aim of this study was to investigate the scope and severity of the second victim problem among nurses by examining the experiences and effects of patient safety incidents (PSIs) on them. Participants/setting: 492 nurses who had experienced PSIs and provide direct care in South Korean medical institutions. Design: A cross-sectional study with anonymous online self-report questionnaires was conducted to nurses in order to examine the experiences and effects of PSIs. Scales measuring post-traumatic stress disorder (PTSD) and post-traumatic embitterment disorder (PTED) were used for a more quantitative examination of the effects of PSIs. A χ 2 test was administered to find any difference in responses to difficulties due to PSIs between the direct and indirect experience of PSIs. Furthermore, linear regression analysis was conducted to investigate the factors related to scores on the PTSD and PTED scales. Results: A statistically significant difference was observed for participants who reported having experienced sleeping disorders, with those with direct experience showing 42.4% sleeping disorders and indirect experience at 21.0%. Also, there was a statistically significant difference between the 34.3% with direct experience and the 22.1% with indirect experience regarding having considered duty or job changes (resignation). Regression analysis showed total PTSD scores for indirect experience at 11.97 points (95% CI: −17.31 to −6.63), lower than direct experience. Moreover, those who thought the medical error was not involved in PSI had a total PTED score 4.39 points (95% CI: −7.23 to −1.55) lower than those who thought it was involved. Conclusions: A considerable number of nurses experienced psychological difficulties due to PSIs at levels that could interfere with their work. The effect of PSIs on nurses with direct experience of PSIs was greater compared with those with indirect experience. There need to be psychological support programmes for nurses to alleviate the negative effects of PSIs.